Application Of Snowball Throwing Model Learning To Improve Social Studies Learning Outcomes For Class Vi Students At SD Negeri 0807 Tanjung Baru - Zakiah Cemerlang Nasution (Indonesian Journal of Basic Education, 2022)
This research is motivated by the low student learning outcomes in social studies subjects. This happens because the teacher does not use a different learning model and does not use the potential of students to provide material, and students are less cooperative in their learning. This research uses qualitative and quantitative methods. The results of the study increased the assessment of lesson plans from 81% to 97%, teacher ratings from 82% to 97%, and student ratings from 75% to 95%. The average academic achievement of students ranged from 72 to 86. It was concluded that the snowball throwing model improved the social studies learning achievement of 6th graders at SD Negeri 0807 Tanjung Baru